Métodos de debicagem em poedeiras comerciais - Santos, Tiago Antônio dos [UNESP] (2014)
The experiment was conducted to evaluate the performance of chicks debicadas by infrared radiation and hot blade. Therefore, we used 800 chicks in the growing period (1-34 days) in a randomized block design, factorial 2 x 3 + 2 (two intensities of beak trimming, moderate and severe, through infrared radiation with three light intensities infrared, low (42 nm), medium (46 nm) and high (52 nm) and two additional treatments of hot blade beak trimming by, and intensity of moderate and severe beak trimming) totaling eight treatments with five replicates of 20 birds / each. The characteristics were the initial weight, cumulative feed intake, weight gain, feed conversion, body weight, uniformity of weight, length and uniformity of the nozzle, feasibility and absence of cannibalism. Data were analyzed by ANOVA, to experiment in a factorial design with additional treatments. In case of significant effect (p <0.05) pairs of means were compared by the F test, and for multiple comparisons was used the Tukey test. For both treatments, the moderate pecking showed better values in feed intake and body weight, however it was observed lower feed conversion debicadas birds by hot blade. Debicadas birds through infrared radiation performed better value, with no difference in feed conversion when compared to the conventional method using pecking hot blade